Perceived social media marketing activities and consumer-based brand equity - Koay, Kian Yeik *; Ong, Derek Lai Teik *; Khoo, Kim Leng *; Yeoh, Hui Jing * (Emerald, 2021)
Purpose: The purpose of this research is to investigate the influence of perceived social media marketing activities on consumer-based brand equity, mainly predicated on the S-O-R model. Furthermore, brand experience is tested as a mediator of the relationship between perceived social media marketing activities and consumer-based brand equity, whereas co-creation behaviour is also examined as a moderator on the relationship between perceived social media marketing activities and brand experience. Design/methodology/approach: A structured survey questionnaire was developed and distributed to social media users from a large private university in Malaysia. A total of 253 valid responses were obtained. Hypotheses were tested employing partial least squares structural equation modelling (PLS-SEM). Findings: The results indicated that perceived social media marketing activities have a significant positive influence on consumer-based brand equity. In addition, brand experience mediates the relationship between perceived social media marketing activities and consumer-based brand equity. Surprisingly, co-creation behaviour was found to have no moderating effect on the relationship between perceived social media marketing activities and brand experience. Furthermore, using the PROCESS macro, we found that the indirect effect of perceived social media marketing activities on consumer-based brand equity through brand experience is not moderated by co-creation behaviour. Originality/value: This research further extended the current knowledge by demonstrating that the influence of perceived social media marketing activities on consumer-based brand equity is mediated by brand experience. Also, this research utilised the strength of PLS–SEM in dealing with higher-order constructs, allowing us to develop and test a parsimonious model that is useful for practitioners.